Effect of iron oxide and silver nanoparticles on boar semen CASA motility and kinetics - BASIOURA, A.; MICHOS, I.; NTEMKA, A.; KARAGIANNIS, I.; BOSCOS, C.M. (Journal of the Hellenic Veterinary Medical Society, 2020)
The objective of the study was to investigate the potential toxic effect of iron oxide (Fe3O4) and silver (Ag/Fe) spherical nanoparticles (NPs) as alternative antimicrobial compounds on boar semen. The NPs’ minimum inhibitory concentration was determined applying the in vitro antimicrobial activity evaluation test and included in the experiment. Totally, 9 ejaculates (3 boars; 3 ejaculates/boar) were extended in BTS without antibiotics at 30×106 spermatozoa/mL and divided in 3 aliquots corresponding to the following groups: 1) Control group (C): extended semen without treatment; 2) Iron oxide group (Fe): extended semen with Fe3O4 NPs of diameter 40 nm (0.192 mg/mL semen); and 3) Silver group (Ag): extended semen with Ag/Fe NPs of diameter 30 nm, consisted of Ag and a 5% of zero-valent Fe (0.128 mg/mL semen). Semen samples of all groups were incubated at 17o C for 30 min following NPs’ removal through a magnetic field. All post treated samples were stored at 17o C for 48 h. Total motility (TM) and kinetics (progressive motility PM; rapid/medium/slow movement spermatozoa; static spermatozoa; VCL; VSL; VAP; LIN; STR; WOB; ALH; BCF; hyperactive spermatozoa) were evaluated by CASA system at 0, 24 and 48 h post treatment. Data were analyzed with a repeated measures mixed model. Group Fe did not differ from group C at any time point. TM and PM were lower at 24 h of storage in group Ag compared to groups C and Fe (all P<0.001). By 48 h of storage spermatozoa of group Ag were totally immotile and thus excluded from analysis. The comparison within groups and between storage time points showed that the values of TM, PM, VCL, VAP, ALH and BCF decreased after 24 h of storage in group Ag (all P<0.05), but not in groups C and Fe, while no significant differences were observed for the remaining parameters between successive time points within any group (P>0.05). In conclusion, Ag/Fe NPs demonstrated a harmful effect on boar spermatozoa, while the used concentration of the examined Fe3O4 NPs did not affect boar sperm CASA motility parameters enhancing further research about their application on semen handling.